Penerapan Pendidikan Karakter dalam Membentuk Kepribadian Santri di Pesantren - Atmawarni Atmawarni (Keguruan, 2022)
This article is a result of research using descriptive qualitative research methods. The purpose of this study was to describe the application of character education in forming a santri personality at the Raudhatul Hasanah Islamic Boarding School. Based on the data obtained that have been analyzed, there are several research findings, namely (1) character education in Islamic Boarding Schools Raudhatul Hasanah was carried out through learning activities and activities outside of learning; (2) the role of Islamic boarding school leaders, Ustadz and Ustadzah are very important, is an example of an example For santri besides being a motivation and inspiration giver; (3) character education in Islamic Boarding School Raudhatul Hasanah is described in the form of various activities, namely: self-development activities, habituation, exemplary, discipline and cultivation.